Effectiveness of Prison Sentences in Preventing Narcotics Crimes - Nasution, Ingka Harsani; Suzuki, Ren; Fujita, Miku (Rechtsnormen: Journal of Law, 2025)
Background: Narcotics-related crimes continue to be a significant issue worldwide, with prison sentences often viewed as a primary deterrent. However, there is limited empirical evidence regarding the effectiveness of incarceration in reducing the incidence of narcotics crimes. The question remains whether prison sentences lead to long-term reductions in drug-related offenses or merely function as a short-term punitive measure without addressing underlying issues such as addiction and socio-economic factors. Objective: This study aims to evaluate the effectiveness of prison sentences in preventing narcotics crimes, focusing on recidivism rates and rehabilitation outcomes for offenders. The research investigates whether incarceration contributes to long-term crime prevention or if alternative approaches, such as rehabilitation programs, offer more sustainable results. Method: A mixed-methods approach was employed, combining quantitative data analysis of recidivism rates from convicted drug offenders and qualitative interviews with legal professionals, offenders, and rehabilitation experts. The data collected spans a five-year period and includes case studies from various correctional facilities. Results: The findings indicate that while prison sentences temporarily reduce narcotics crime, they are less effective in preventing recidivism. Rehabilitation programs integrated into the prison system significantly contributed to reducing reoffending rates, particularly when combined with post-release support. Conclusion: Prison sentences alone are insufficient in preventing narcotics crimes. A more comprehensive approach, including rehabilitation and social reintegration efforts, is necessary for long-term success in reducing narcotics-related offenses.